Dielectric response and relaxation phenomena in composites of epoxy resin with BaTiO3 particles - Ramajo, Leandro Alfredo (2005)
Dielectric properties and relaxation phenomena of composite materials (epoxy resin - barium titanate) were studied as a function of ceramic content. The composites were prepared mixing both components and pouring them into suitable moulds. Some composites were made using tetrahydrofuran (THF) because it helped to reduce matrix viscosity, facilitating the system mixture. Dielectric measurements showed that dielectric constant of composites depended on the filler amount, the temperature and the frequency. Dielectric losses also were influenced by the temperature and by the frequency through relaxation process, even though volume fractions did not have influence on losses.